Medical mistrust is related to lower longitudinal medication adherence among African-American males with HIV - Dale, Sannisha K; Bogart, Laura M; Wagner, Glenn J; Galvan, Frank H; Klein, David J (Journal of health psychology, 2016)
African-Americans living with HIV show worse health behaviors (e.g. medication adherence) and outcomes (e.g. viral suppression) than do their White counterparts. In a 6-month longitudinal study, we investigated whether medical mistrust among African-American males with HIV (214 enrolled, 140 with longitudinal data) predicted lower electronically monitored antiretroviral medication adherence. General medical mistrust (e.g. suspicion toward providers), but not racism-related mistrust (e.g. belief that providers treat African-Americans poorly due to race), predicted lower continuous medication adherence over time (b = −.08, standard error = .04, p = .03). Medical mistrust may contribute to poor health outcomes. Intervention efforts that address mistrust may improve adherence among African-Americans with HIV.